2014
DOI: 10.1155/2014/341365
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tribological Behavior of Carbon Nanotube Based Industrial Mineral Gear Oil 250 cSt Viscosity

Abstract: The paper investigates the exceptional antiwear and extreme pressure properties of multiwalled carbon nanotube based mineral oil. Different samples of oil containing varying proportions of MWNT (MWNT) and graphite were prepared. The samples were tested for their antiwear and load bearing capacity according to ASTM G99 and ASTM D-2783 standards. After pass load test in four ball tester the rubbed surfaces were investigated with Scanning Electron Microscope (SEM) images. The wear test results show a decrease wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Many researchers have reported that the addition of nanoparticles can improve the tribological properties of pure oil. Nanoparticles that have been employed as pure oil additive are graphite [2][3][4], molybdenum disulfide [5][6][7], and carbon nanotubes [8][9][10]. Huang et al [11] synthesized graphite nanosheets with average diameter of 500 nm by stirring ball milling and evaluated the tribological properties of graphite nanosheets as paraffin oil additive.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that the addition of nanoparticles can improve the tribological properties of pure oil. Nanoparticles that have been employed as pure oil additive are graphite [2][3][4], molybdenum disulfide [5][6][7], and carbon nanotubes [8][9][10]. Huang et al [11] synthesized graphite nanosheets with average diameter of 500 nm by stirring ball milling and evaluated the tribological properties of graphite nanosheets as paraffin oil additive.…”
Section: Introductionmentioning
confidence: 99%
“…Among nanocarbons, carbon nanotubes (CNTs) show good antiwear and antifriction properties even under heavy load conditions, which makes them a valid alternative to the traditional lubricant 2 of 15 additives [12][13][14][15][16]. Along with CNTs, graphene, a 2D nanomaterial with a hexagonal honeycomb crystalline structure made up of sp 2 hybridized carbon atoms, has shown remarkable antiwear and antifriction properties due to its multilayer morphology, as well as due to its ability to increase a convective heat transfer in the base oil as a result of its high thermal conductivity [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the macro sized additives have been replaced by nano-sized additives which have been reported in literatures. These are nano-sized Cu, CuO, TiO 2 , CeO 2, ZnO, Al 2 O 3, SiC, nano-diamond, graphite, molybdenum disulphide, tungsten disulphide etc (Zhou et al, 1999;Zhou et al, 2001;Bahadur et al, 2005;Barttez et al, 2006;Thottackkad et al, 2014;Bhaumik et al, 2014;Pisal et al, 2014;Pathak et al, 2015). In order to stabilize the nano-sized particles or to protect the growth of particle size or to overcome the spontaneous coalescence, surfactants have been used along with nanoadditives.…”
Section: Introductionmentioning
confidence: 99%
“…In order to stabilize the nano-sized particles or to protect the growth of particle size or to overcome the spontaneous coalescence, surfactants have been used along with nanoadditives. Polyethylene glycol, lauryl sodium sulfate, triton X-100 etc are the surfactants generally used for the surface modification of the prepared nano-sized additive (Zhou et al, 1999;Zhou et al, 2001;Bahadur et al, 2005;Barttez et al, 2006;Thottackkad et al, 2014;Bhaumik et al, 2014;Pisal et al, 2014;Pathak et al, 2015). In this study, we try to prepare CuO nanoadditives for engine oil and lauryl sodium sulfate as surfactant.…”
Section: Introductionmentioning
confidence: 99%